Some facts about business cycles synchronisation across the euro area countries: the case of small countries - Correia, Leonida (2011)
According to Optimum Currency Area literature, the synchronisation of business cycles is necessary for the successful implementation of a common monetary policy. This paper contributes to this debate, providing a descriptive analysis of the euro area business cycle synchronisation, using quarterly real GDP series, spanning from 1980:1 to 2004:4, for nine euro area countries. We consider the four largest countries (Germany, France, Italy and Spain), which account for almost 80% of the euro area GDP, and five among the smallest countries, Belgium, Finland, Greece, the Netherlands and Portugal. Our aim is to see whether the synchronisation and the amplitude of the business cycles across the Member States increased with the monetary integration process. We will give greater focus to small countries compared to what can be seen in existent literature. Overall, we found that the business cycles association for all nine countries considered from 1980 to 2004 is positive and significant. Moreover, evidence suggests that with the creation of the euro, business cycles became more correlated among the larger countries of the euro area, which is consistent with the hypothesis of endogeneity of the Optimum Currency Area criteria. Contrarily, the group of small countries is very heterogeneous and still presents different degrees of synchronisation with the euro area business cycle. Also, after 1997, the degree of synchronisation with the euro area business cycle has been reduced. This result indicates that the monetary policy of the European Central Bank, in place since 1999, has not been adjusted for some of the small countries of the euro area. The divergence of the Portuguese business cycle experienced in the recent past is of major concern.